“To Suffer in Paradise”: Feelings Mothers Share on Portuguese Facebook Sites - César, Filipa; Costa, Patrício; Oliveira, Alexandra; Fontaine, Anne Marie (Frontiers in Psychology, 2018)
Background: Motherhood is an emotional rollercoaster. This is overlooked by most literature, which tends to refer mothers’ pathological states of postpartum depression and anxiety, mainly seeking to understand their causes or predicting factors, and consequences on children’s development. Objective: In this study, we aim to observe the diversity of mothers’ emotional states, and to analyze both positive and negative feelings they disclose on specific public and closed motherhood sites on Facebook. We hypothesize that the intensive motherhood model is prevalent in Portuguese society, thus influencing the type of feelings and circumstances in which mothers disclose them. Method: We collected posts and comments from the four most popular Portuguese Facebook motherhood sites during 2015 and, then, conducted a quantitative and content analysis to identify the expressed range of feelings concerning motherhood. Results: Mothers preferably share their positive feelings on public pages, whereas negative feelings are shared more in closed groups. Expressed positive and negative feelings are different whether we look at normative or non-normative, public or closed sites. Discussion: We assume that motherhood sites on Portuguese Facebook reflect an intensive motherhood model that is normative in Portuguese society. Positive feelings towards children are promoted and openly shared in public normative sites, while negative feelings concerning motherhood are dealt with in the privacy of closed groups. We propose an extensive motherhood model to overcome this duality and to allow women to pursue several different social roles simultaneously in an equally rewarding way.